Towards a conceptual description of rehabilitation as a health strategy - Meyer, Thorsten; Gutenbrunner, Christoph; Bickenbach, Jerome; Cieza, Alarcos; Melvin, John; Stucki, Gerold (Journal of rehabilitation medicine, 2011)
A proposal for a conceptual description of rehabilitation was made in 2007 based on the International Classification of Functioning, Disability and Health. This conceptual description should foster the development of a common understanding of rehabilitation and its professions. The present paper aims to report on the development and current state of the discussions about this conceptual description and to provide the current version, which has been adopted by different European professional and scientific organizations. First, the history of the development of the conceptual description of rehabilitation is reported. Secondly, suggestions for modifications or amendments are introduced, and the resulting phrases and terms are presented and discussed. One major change to the conceptual description of rehabilitation is the explicit integration of the perspective of the disabled person. The relationship between person and provider is characterized as a partnership. However, it is argued that quality of life should not be introduced as a primary goal of rehabilitation. This conceptual description can foster a common understanding of the rehabilitation professions and provide a point of departure for clarifying the role of different professions and services within the broad field of rehabilitation. It can also serve to position rehabilitation as a major health strategy and to sharpen the perception of rehabilitation among external stakeholders.